Croatian "Judiths" - Vigato, Teodora; Srebrović, Katarina (Anafora, 2022)
In this paper, the authors deal with various interpretations in Croatian literature of the biblical Judith and Marulić’s Judith. They begin with the story of Judith from Zadar whose anonymous authors had the task to spread the biblical story of the courageous Judith. Then they speak about Judith in the works of Antun Gleđević and Ignjat Đurđević, in the Baroque literature of Dubrovnik, in the context of the Dubrovnik melodramatic or pseudolibretistic production. The paper highlights the Slavonian Judith, that is, her interludes and concludes with the contemporary Judiths of Miro Gavran and Boris Senker. The biblical text has served also as an inspiration for various interpretations in a wide range of performances, from musical to puppet theatre. Each author followed the point of view, the artistically specific, poetic, structural and technical requirements of the genre and placed the main character and her story in a new intertextual or media content.